ADOLESCENT’S HEALTH EDUCATION ABOUT THE SEX INFORMATION ON PREMARITAL SEX’S PERCEPTION (study in nagara vacational school of kedunggalar District, Ngawi) - Tika Dwi Rahayu; Rahaju Ningtyas; . Agustina M.R. (STIKES Insan Cendekia Medika Jombang, 2015)
The globalization era is a development era in all sector, one of them is the rapiddevelopment ofthemediaandwithin easy reach. In very rapid development give positive and negative impact.The negativeimpact, arisingfrom the development ofadvancedmediafor teensisgetting easierto find information, especiallyabout sexisconsidered to bea new thingfor teenagers. In can increase premaritalsexrate isincreasingeveryyear. This research aims to know the effect of adolescent’s health education about the sexinformation on premarital sex perception in SMK Nagara district of Kedunggalar Ngawi regency.Research design was Non Eksperimen – one group pre intervensi and post test design. The population wasall adolescents in class 10 of SMK Nagara district of Kedunggalar Ngawi regency as many as 200 studentsand the samples were 133 students. The data collection technique used was Proportional simple randomsampling. The independent Variablewas the effect of reproduction health education of adolescent about sex,while the dependent was the premarital sex perception. The instruments used in this research wasaquetionaire, data processing used by Editing, coding,scoring,tabulating,analisa bivariat,univariat and testedby wilcoxon.The result obtained that before being conducted health education the adolescent’s perception on premaritalsex was most positive 73 respondents (54,9 %) and after being conducted health education the adolescent’sperception on premarital sex became negative was 86 respondents (64,6%). It was obtained p value 0,002 <0,05so Ho rejected and H1 accepted which means that there is an effect of health education about sexinformation on premarital sex perception.